UNA DECADA DE PARTICIPACION DEL PRODUCTO INTERNO BRUTO Y SU IMPACTO EN LOS INDICADORES ECONOMICOEMPRESARIALES - Rojas Silva, Hugo Roberto; Bizarron, Manuel Ernesto Becerra; Delgado Díaz, Luz Amparo (European Scientific Journal, ESJ, 2014)
This paper analyzes the economic participation of a municipality with a concentration in a single economic activity (tourism), and its importance in the generation of wealth, we analyze the caseof Puerto Vallarta, Jal.. It uses a program model used by the United Nations Development Programme (UNDP) for the determination of gross domestic product, gross domestic product by sector, we get the shares to the State as well as GDP per capita, and finally discusses the evolution of these variables in the period 2000 to 2009. The results indicate that there is empirical evidence in the real indicators of the study period, so it can be used as a reference for public policy to improve the performance of these indicators.